2016
DOI: 10.14719/pst.2016.3.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pteridophyte Diversity and their Status in Gujarat State, Western India

Abstract: An intensive field survey was carried out from the hilly regions, plains of different climatic regimes and agricultural land of Gujarat state. About 23 species were collected from Gujarat state, from which eight species viz., Actiniopteris radiata (Sw.) Link, Adiantum caudatum L., A. incisum Forssk., Lygodium flexuosum (L.) Sw., Pteris vittata L., Selaginella ciliaris (Retz.) Spring, S. delicatula (Desv. ex Poir.) Alston, and S. repanda (Desv. ex Poir.) Spring. were added as new distributional record for the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Later few studies were done by Patel et al, (2010), Dabgar (2012), and Modi and Dudani (2013).In 2015, Modi published a paper which documented the presence of 16 species in Gujarat. Rajput et al, (2016) assessed the pteridophyte diversity of Gujarat through a field study of three years, in which 23 species were collected. It was also noted that Equisetum debile was extinct from the wild and Isoetes coromandeliana was on the verge of extinction.…”
Section: Pteridophyte Diversity In the Six States Traversed By The Western Ghatsmentioning
confidence: 99%
“…Later few studies were done by Patel et al, (2010), Dabgar (2012), and Modi and Dudani (2013).In 2015, Modi published a paper which documented the presence of 16 species in Gujarat. Rajput et al, (2016) assessed the pteridophyte diversity of Gujarat through a field study of three years, in which 23 species were collected. It was also noted that Equisetum debile was extinct from the wild and Isoetes coromandeliana was on the verge of extinction.…”
Section: Pteridophyte Diversity In the Six States Traversed By The Western Ghatsmentioning
confidence: 99%
“…Similarly, 28 Pteridophytic species belonging to 13 families were collected from Rani Ban of Kaski, Nepal in June ,2015 which is reported in' An annual progress report' published by KATH (Annual progress report 2014-15, www.kath.gov.np). Altogether, 23 species of Pteridophytes were documented from Gujarat state of western India and out of which Equisetum debile and Isoetes coromandelina are in the state of extinction (Rajput et al, 2016). A total of 105 species of Pteridophytes under 19 families and 45 genera were recorded from Manaslu Conservation area (Bhattarai & Rajbhandary, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The pteridological studies were carried out by various researchers in the Gujarat (9-16) and a single species (i.e. A. hohenackerianum T. Moore) is reported previously from Gujarat state (17).…”
Section: Introductionmentioning
confidence: 99%
“…biserrulatum (Christ) Fraser-Jenk., belonging to the family Athyriaceae. Perusals of available literature on pteridophyte diversity of Gujarat showed that occurrence of these four ferns were not documented so far in the existing list of the pteridophyte diversity of Gujarat state (12,17,(18)(19)(20). Therefore, a brief description and photograph (Fig.…”
Section: Introductionmentioning
confidence: 99%